Therareach: A Synergized Therapy and Counseling Access Framework for Learners with Special Needs - Jocyn T. Sepada; Maria Katrina P. Batusbatusan; Christianlie G. Quitayen; Janine Joy Tenerife-Caňete; Honorio C. Anora; Julius C. Taghoy; Reylan G. Capuno; Raymond C. Espina; Irene O. Mamites; Randy C. Mangubat (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This study explored the feasibility, acceptability, and potential impact of the THERAReach framework in supporting SPED learners at Bato Elementary School in Toledo City. Employing a qualitative exploratory case study design, data were collected from diverse stakeholders, including SPED teachers, parents, school administrators, guidance counselors, and community service providers, through interviews and focus group discussions. Guided by Bronfenbrenner’s Ecological Systems Theory, Maslow’s Hierarchy of Needs, and Vygotsky’s Sociocultural Theory, the study examined the availability of therapy and counseling services, barriers to access, and the perceived impact of limited support on learners’ well-being, development, and academic outcomes. Findings revealed reliance on SPED teachers and guidance counselors for basic psychosocial support, with specialized services often accessed externally. Major barriers included the lack of on-site licensed professionals, long referral wait times, financial and travel burdens, inadequate facilities, and teacher overload. These gaps contributed to delayed diagnoses, skill regression, behavioral challenges, teacher burnout, and family disengagement. Stakeholders emphasized the importance of structured frameworks, regular counseling schedules, crisis protocols, confidential therapy spaces, teacher training, and partnerships with LGUs and NGOs. The THERAReach framework was considered acceptable and potentially transformative, contingent on adequate funding, staffing, and collaborative support. The study highlights the need for an inclusive, sustainable, and contextually responsive model to enhance therapy and counseling services for SPED learners.